2020
DOI: 10.1002/aenm.202002215
|View full text |Cite
|
Sign up to set email alerts
|

Amorphous/Crystalline Heterostructured Cobalt‐Vanadium‐Iron (Oxy)hydroxides for Highly Efficient Oxygen Evolution Reaction

Abstract: The oxygen evolution reaction (OER) is a key process involved in energy and environment‐related technologies. An ideal OER electrocatalyst should show high exposure of active sites and optimal adsorption energies of oxygenated species. However, earth‐abundant transition‐metal‐based OER electrocatalysts still operate with sluggish OER kinetics. Here, a cation‐exchange route is reported to fabricate cobalt‐vanadium‐iron (oxy)hydroxide (CoV‐Fe0.28) nanosheets with tunable binding energies for the oxygenated inter… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

7
139
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 230 publications
(146 citation statements)
references
References 45 publications
7
139
0
Order By: Relevance
“…Layered double hydroxides (LDHs) have been considered as the promising candidate with satisfying performance toward OER especially in alkaline water splitting, [ 16–21 ] which can be described by the general formula [M 2+ 1− x M 3+ x (OH) 2 ] x + (A n − ) x / n · y H 2 O (M 2+ and M 3+ are divalent and trivalent metals in the positively charged host layers; A n − is the interlayer anion for charge compensation). Typically, the edge‐sharing metal‐O 6 octahedral host layer has turned out to be the active center for oxygen‐evolving process.…”
Section: Introductionmentioning
confidence: 99%
“…Layered double hydroxides (LDHs) have been considered as the promising candidate with satisfying performance toward OER especially in alkaline water splitting, [ 16–21 ] which can be described by the general formula [M 2+ 1− x M 3+ x (OH) 2 ] x + (A n − ) x / n · y H 2 O (M 2+ and M 3+ are divalent and trivalent metals in the positively charged host layers; A n − is the interlayer anion for charge compensation). Typically, the edge‐sharing metal‐O 6 octahedral host layer has turned out to be the active center for oxygen‐evolving process.…”
Section: Introductionmentioning
confidence: 99%
“…For example, amorphous RuTe 2 porous nanorods and NiFeMo oxides have been fabricated for water splitting [10, 11] . Although amorphous materials have intrinsic high activity, the low electrical conductivity severely limits their charge transfer kinetics [12] . Therefore, the development of new noble‐metal‐free electrocatalysts is vitally in demand.…”
Section: Introductionmentioning
confidence: 99%
“…[15,16,21,22] Compared with unary and binary metal oxides, trimetallic oxides, especially those featured with the introduction of a third metallic element with high valence, can achieve effectively modulated electronic structure, optimizing the adsorption energy of reaction intermediates and thereby promoting the catalytic activity. [23,24] For example, Sargent and co-workers reported that introduction of non-3d metal W with high-valence High theoretical specific energy of rechargeable lithium-oxygen (Li-O 2 ) batteries makes them very promising in the development of long driving range electric vehicles and energy storage on large-scale. However, the large polarization and poor cycling stability associated with insufficient catalytic cathodes and the insulating nature of discharge products limit their practical applications.…”
Section: Introductionmentioning
confidence: 99%